Editorial - Osmani, Noor Mohammad (IIUM PRESS, 2024)
Al-Burhan issue of August 2024 covers a wide range of topics based on the Qur’an and Sunnah. It ranges from ‘social proof in Qur’an and Sunnah’, ‘e-commerce and sunnah’, ‘criticism of hadith text in Indonesia’, ‘Maqasidul Qur’an and Rashid Rida’, ‘Qur’anic manuscripts in Qatar’, ‘Abu Hanifah and the Sunnah of the Prophet’, ‘crisis of poverty in Afghanistan and Qur’anic solution’, ‘corporal punishments based on Qur’an and Sunnah’ and ‘peaceful coexistence and the verses of abrogation in the Qur’an’. Hence, the issue will cover different issues from various angles but derived from the Qur’an and Sunnah, the primary sources of Islam.